Testosterone challenge and androgen receptor activity in relation to UGT2B17 genotypes. (7th January 2013) - Ekström, Lena; Cevenini, Luca; Michelini, Elisa; Schulze, Jenny; Thörngren, John‐Olof; Belanger, Alain; Guillemette, Chantal; Garle, Mats; Roda, Aldo; Rane, Anders
Abstract Background We investigated the androgen receptor (AR) bioluminescense response in serum and urine before and after testosterone challenge in different genotypes of the UGT2B17 enzyme, which catalyses testosterone glucuronidation. Material and methods The androgen receptor activity was determined using a yeast‐based bioluminescence assay. The androgens were analysed using LC‐MS/MS, and the individuals were genotyped for UGT2B17 deletion polymorphism using real‐time polymerase chain reaction. Results The serum concentrations of testosterone and dihydrotestosterone (DHT) were markedly elevated on days 2 and 4 and were still above baseline on day 15 after a dose of 500 mg testosterone enanthate. The androgenic activity in serum increased in parallel and correlated with the hormone concentrations and remained above baseline on day 15. The urinary androgenic activity increased 4–5‐fold and was closely related to the unconjugated testosterone and independent of the UGT2B17 genotype. Conclusions The AR assay may serve as a complement to the urinary testosterone/epitestosterone (T/E) doping test, because this is profoundly influenced by the UGT2B17 deletion polymorphism. It may also be useful for detection of other illicit androgens in sports, or in the society, or for monitoring and diagnostics of androgen‐related disorders.